Inverted-L Antenna (ILA) Design Using Fractal for WLAN USB Dongle - Luo, Qi (2013)
This work presents an Inverted-L antenna design using the fractal geometry for dual band WLAN (2.4/5.2GHz) USB dongle application. The proposed antenna has the advantages of compact size, wide operation bandwidth and easy fabrication. The experimental results show that it has a S11<-10 dB bandwidth from 2.25 to 2.60 GHz and 5.06 to 5.62 GHz. The radiation performances of the proposed antenna in free space and when connected to a laptop computer were also studied in this work. The proposed antenna was designed and optimized by using Ansoft HFSS V13.